Effect of the microtubule-associated protein tau on dynamics of single-headed motor proteins KIF1A - Sparacino, Javier; Farías, María Gimena; Lamberti, Pedro Walter (2021)
Fil: Sparacino, Javier. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.